KONSEPTOR PEREKONOMIAN INDONESIA DI MASA ORDE BARU TAHUN 1968-1998 - Indah, Seyusa Viora; ', Isjoni; ', Kamaruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: After Soeharto and his supporters succeeded in seizing power from President Soekarno, automatic legacy of bad economic conditions became a major challenge President Soeharto to immediately fix the situation. The start of President Soeharto's government in the economic field is the implementation of a western-style economy pioneered by Indonesian economists who had studied at the University of California Barkeley. The purpose of this study is to examine who and how the designers of the Indonesian economy in the New Order period of 1968-1998. The method used in this research is historical and descriptive method. Data obtained through literature techniques, documentation and comparative studies. The location of research is in the city of Pekanbaru Riau. The time of study from the start of the proposal seminar to the thesis examination. The result of this research is that when the Old Order government fell, the New Order government was led by President Soeharto, especially the economic field of President Soeharto handed over his management to a group of Barkeley economists such as Widjojo Nitisastro, the leader of the Barkeley group, and Emil Salim, Ali Wardhana, JB Sumarlin , DorodjatunKuntjoro-Jakti with a position as a group of Barkeley economists whose task is to manage the Indonesian economy with the Capitalist system and use foreign loans for development during the New Order. As a result, the Indonesian economy is heavily dependent on the rupiah exchange rate against the dollar, given Indonesia pays foreign debts with the dollar. And when the economic crisis of 1998, Indonesia's economy slumped one of the causes of the game dollar currency.Keywords: Drafter, Economy New Order.